APPLICATION OF MNEMONIC LEARNING METHODS IN IMPROVING STUDENTS' MUFRADAT REMEMBER AT MTS NEGERI 1 PROBOLINGGO - Junainah, Siti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The research aims are as follows: (1) to find out the implementation of the Mnemonic Learning method in improving students' short-handed memory (2) to find out what are the supporting facts of the Mnemonic Learning method in improving students' shorthanded memory, (3) to find out what the quality of the Mnemonic Learning method is in improve students' mufradat memory.